Do elite colleges matter? The impact on entrepreneurship decisions and career dynamics - Naijia Guo; Charles Ka Yui Leung (Osaka University, Institute of Social and Economic Research (ISER), 2021)
Elite college attendance significantly impacts students' entrepreneurship decisions and career dynamics. We find that an elite college degree is positively correlated with entrepreneurship (i.e., owning an incorporated business) but not with other self-employment forms. Our overlapping generations model captures self-selection in education and career choices based on heterogeneous ability and family wealth endowments over the life-cycle. Our estimates show that (1) entrepreneurs and other self-employed individuals require different types of human capital, and (2) elite colleges generate considerably more human capital gain than ordinary colleges, particularly for entrepreneurs. Distinguishing between elite and ordinary colleges improves our prediction of entrepreneurship decisions. Providing subsidies for elite colleges is more efficient than subsidizing their ordinary counterparts to encourage entrepreneurship, enhance intergenerational mobility, and enhance welfare. In contrast, although start-up subsidy increases entrepreneurship, it does not improve their performance, and it is inferior to education subsidy in generating efficiency, equality, and intergenerational mobility.
Keywords: D15; I20; J24; 330; entrepreneurship; elite college; intergenerational transfer